1993
DOI: 10.1111/j.1741-6248.1993.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Family Business Consultants—Who We Are, What We Do, and How We Do It

Abstract: This research note compares data from two surveys of members of the Family Firm Institute conducted during 1990 and 1991 and relates these data to the issues confronting family business as an emerging field. One survey, sent to all Family Firm Institute members, requested demographic data and information pertinent to the Family Firm Institute strategic planning committee. The second survey, sent to those members of Family Firm Institute who self‐identified as service professionals, was designed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 9 publications
2
41
0
1
Order By: Relevance
“…This concept of multidisciplinary advising is similar to Leo Danco's notion of a "council of advisors," in which advisors are encouraged to meet and act collectively in order to provide better solutions for their family business clients (Sidwell, 1989). Other researchers, meanwhile, have suggested that technical and nontechnical advisors work together to come up with different insights and generate better solutions (e.g., Upton et al, 1993). More recently, Hilburt-Davis and Dyer (2003) suggested that family business advisors work at the boundaries where the family, business, and ownership systems overlap.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
See 2 more Smart Citations
“…This concept of multidisciplinary advising is similar to Leo Danco's notion of a "council of advisors," in which advisors are encouraged to meet and act collectively in order to provide better solutions for their family business clients (Sidwell, 1989). Other researchers, meanwhile, have suggested that technical and nontechnical advisors work together to come up with different insights and generate better solutions (e.g., Upton et al, 1993). More recently, Hilburt-Davis and Dyer (2003) suggested that family business advisors work at the boundaries where the family, business, and ownership systems overlap.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…Family business advisors need to have a different set of skills, including skills that allow them to manage family dynamics and deal with family conflicts, among others. Family business advisors also need to balance the needs of the business and the concerns of the family when providing advising services (Upton et al, 1993).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The advising process differs in family firms as advisors must navigate themselves through overlapping family and business systems that result in intersecting personal and business conflicts (Bork et al, 1996), increased cognitive challenges, longterm emotional needs, and complex interrelationships with conflicting stakeholder interests (Gersick et al, 1997;Jaffe & Lane, 2004). Authors have identified fundamental differences between family and nonfamily firms that have implications for the advising process, how advisors intervene, and the advising tools they utilize (see Table 1; Upton et al, 1993).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Yet, as expressed by one advisor that "If nobody knows who I am, or what I do, then I know I'm doing my job," their advice can also be quite subtle (Dutton, Ashford, O'Neill, Hayes, & Wierba, 1997). Notwithstanding the recognized importance of the use of advisors and advice networks in family business (e.g., Astrachan & McMillan, 2006;LaChapelle & Barnes, 1998;Upton, Vinton, Seaman, & Moore, 1993), there has been limited attention toward developing an understanding of providing subtle advice and the implicit underlying processes through which advisors afford value to family firms. Yet, despite being not easily seen, subtle advice can be vital to the health of the family firm.…”
Section: Introductionmentioning
confidence: 99%